The Influence of Rules and Translation Methods on Students Interest in Learning Arabic in Elementary Schools: Pengaruh Metode Kaidah dan Terjemah Terhadap Minat Belajar Bahasa Arab Siswa di Sekolah Dasar - Isnaini Wahyu Kamilah; Farikh Marzuqi Ammar (Universitas Muhammadiyah Sidoarjo, 2022)
The method of rules and translation in learning a language is a learning that focuses on listening activities to students in the classroom. This study aims to determine how much influence the rules and translation methods have on the interest in learning Arabic in the Matayum 1st grade students at the Darawithaya school in Southern Thailand. This research methodology is a quantitative research. The data collection of this research was obtained by questionnaires/questionnaires, interviews, and document studies. Analysis of the research data using independent T test analysis on the SPSS ©IBM v. application. 24.0.0. The results showed as follows: Based on the results of the calculation of the questionnaire given to students, the data showed that the rules and translation methods in Arabic learning activities at Darawithaya School had an influence in increasing students' learning interest when learning Arabic. translate; Interest to learn.